Randomized Trial of Observation and Execution of Upper Extremity Actions Versus Action Alone in Children With Unilateral Cerebral Palsy. (November 2013) - Sgandurra, Giuseppina; Ferrari, Adriano; Cossu, Giuseppe; Guzzetta, Andrea; Fogassi, Leonardo; Cioni, Giovanni
Background . The properties of the mirror neuron system suggest a new type of upper limb (UL) rehabilitation in children with unilateral cerebral palsy (UCP), based on observation of action therapy followed by execution of a variety of observed movements (AOT). Objective . We tested the effects of AOT in the Upper Limb Children Action Observation Training (UP-CAT) trial. Methods . In a randomized, evaluator-blinded, block-designed trial, 24 UCP children with mild to moderate hand impairment were assigned to 2 groups. The experimental group observed, 1 hour per day for 3 consecutive weeks, video sequences of unimanual or bimanual goal-directed actions and subsequently executed observed actions with the hemiparetic UL or both ULs. The control group performed the same actions in the same order as the experimental sample, but had watched computer games. The Assisting Hand Assessment (AHA) scale was the primary outcome measure; the Melbourne assessment and ABILHAND-Kids were secondary ones. Outcomes were assessed at 1 week (T1), 8 weeks (T2), and 24 weeks (T3) after the end of the training. Results . The experimental group improved more ( P = .008) in score changes for the AHA at the primary endpoints T1 ( P = .008), T2 ( P = .019), and T3 ( P = .049). No between-group significant changes were found for ABILHAND-Kids or Melbourne assessment. Conclusions . UP-CAT improved daily UL activities in UCP children, suggesting a new rehabilitation approach based on a neurophysiological model of motor learning.